2020
DOI: 10.1111/nmo.13874
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green kiwifruit on gas transit and tolerance in healthy humans

Abstract: Background Green kiwifruit is a fiber‐rich fruit that has been shown effective for treatment of constipation. However, fermentation of fibers by colonic bacteria may worsen commonly associated gas‐related abdominal symptoms. Aim: To determine the effect of green kiwifruit on transit and tolerance to intestinal gas in humans. Methods In 11 healthy individuals, two gas challenge tests were performed (a) after 2 weeks on a low‐flatulogenic diet and daily intake of 2 green kiwifruits and (b) after 2 weeks on a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This study found that subjects in the kiwifruit consumption group experienced a significantly greater number of complete spontaneous bowel movements (CSBM) a week, in addition to improved gastrointestinal discomfort, compared with baseline for abdominal pain, constipation, and indigestion [22]. Another recent study conducted by Noemi Caballero et al, investigated the effect of green kiwifruit on transit and tolerance to intestinal gas in 11 healthy subjects [23]. This randomized, cross-over study found that a diet consisting of 2 weeks of daily consumption of kiwifruit, in addition to a low-flatulogenic diet, led to an increase in stool frequency compared to a diet without kiwifruit for 2 weeks.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study found that subjects in the kiwifruit consumption group experienced a significantly greater number of complete spontaneous bowel movements (CSBM) a week, in addition to improved gastrointestinal discomfort, compared with baseline for abdominal pain, constipation, and indigestion [22]. Another recent study conducted by Noemi Caballero et al, investigated the effect of green kiwifruit on transit and tolerance to intestinal gas in 11 healthy subjects [23]. This randomized, cross-over study found that a diet consisting of 2 weeks of daily consumption of kiwifruit, in addition to a low-flatulogenic diet, led to an increase in stool frequency compared to a diet without kiwifruit for 2 weeks.…”
Section: Discussionmentioning
confidence: 93%
“…This study also found that although stool frequency increased in the kiwifruit consumption group, subjects did not undergo associated abdominal symptoms, such as increased rectal gas evacuation, which can occur due to an increase in fiber intake. This study concluded that green kiwifruit can in-crease stool frequency in healthy subjects without the associated effects on intestinal gas transit and tolerance, making it a potential alternative treatment for constipation [23]. In addition to laxative properties, Lee et al wanted to determine how 4 days of kiwifruit consumption would influence intestinal microbiota populations [24].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 229 articles (PubMed: 85; EMBASE: 106; Cochrane Library: 38) were retrieved, and eight of them, describing nine clinical studies, were considered eligible for inclusion in this review [30][31][32][33][34][35][36][37]. The PRISMA flow diagram summarising the article selection process is displayed in Figure 1.…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…The Panel notes that this study with a small sample size and a short duration was not designed to investigate changes in defecation and that the number of kiwifruits consumed in the study was twice the amount proposed in the conditions of use. Caballero et al (2020) carried out a two-period cross-over, randomised, single-blind study to evaluate the effect of consumption of a low-flatulogenic diet (excluding legumes, vegetables, garlic, onion, cucumber, nuts, cereals, whole-meal bread, and fizzy drinks) plus green kiwifruit in comparison to a low flatulogenic diet alone on intestinal gas production (primary outcome), stool frequency, stool consistency and abdominal symptoms. Eleven healthy individuals (8 women; age range 18-23 years) were recruited and all completed the study.…”
Section: Studies In Healthy Individualsmentioning
confidence: 99%
“…Six human intervention studies reported in five publications (Rush et al., 2002; Wilkinson‐Smith et al. 2018; Caballero et al., 2020; Drummond et al., 2020 unpublished study report; Chey et al., 2019) were evaluated by the Panel for the scientific substantiation of the claim. All of them were conducted with green kiwifruit var.…”
Section: Assessmentmentioning
confidence: 99%